Early rule out of acute myocardial infarction - Lindahl, Bertil; Venge, Per (Journal of Laboratory and Precision Medicine, 2017)
Any measures taken to safely reduce the numbers of patients in the crowded emergency room are more than welcome. Patients with suspicion of acute myocardial infarctions (AMI) make up a substantial number of such patients, about 10%, and these patients deserve special attention, since rapid actions are often required in whom the diagnosis of AMI is established. Diagnostic algorithms are continuously upgraded by international expert groups to define the criteria for AMI, i.e., to rule-in the patient and refer him/her to appropriate actions.